Prices and quantities of new products Hungarian firm and product level data - László Halpern (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
This paper analyzes the driving factors of growth of quantities and prices of the new products for Hungarian firms between 2001 and 2016. It investigates how price levels are correlated with firm and market characteristics, and the time path of the share of new products. Larger and more productive firms were able to sell their new products at higher prices, though larger competition had a dampening role. Pricing patterns differ for all products, higher share of foreign ownership leads to lower export and import prices. The share of new products is negatively affected by size corroborated by the negative effect of both productivity and foreign ownership. Productivity does not have any role in price and quantity growth rates.
Keywords: D24; F23; L25; 330; trade; growth; productivity